The design of s-boxes by simulated annealing - Clark, J.A.; Jacob, J.L.; Stepney, S. (2004 IEEE International Conference on Evolutionary Computation, 2004)
Substitution boxes are important components in many modern day block and stream ciphers. Their study has attracted a great deal of attention over many years. The development of a variety of cryptosystem attacks has lead to the development of criteria for resilience to such attacks. Some general criteria such as high nonlinearity and low autocorrelation have been proposed (providing some protection against attacks such as linear cryptanalysis and differential cryptanalysis). There has been little application of evolutionary search to the development of s-boxes. In This work we show how a cost function that has found excellent single-output Boolean functions can be generalised to provide improved results for small s-boxes.